A study on the role of parents and the prevalence of childhood obesity / Nur Amalina Suhaimi, Zaliha Hussin and Rozalli Hashim - Suhaimi, Nur Amalina; Hussin, Zaliha; Hashim, Rozalli (Universiti Teknologi MARA, Shah Alam, 2017)
Obesity is a growing public health concern that occur all around the world. Obesity is one of the indicators of inequality influenced by socioeconomic issue. Childhood obesity may affect long term health of children's development. The role of parents is extremely important in making healthy lifestyle among the children. In Malaysia, the growing rate of obese children happen due to the parents' lifestyle shape among the family. Due to modern lifestyle, the parents are busy with their tight schedule and their behavior for selecting and preparing healthy food choices for their children is limited. This paper presents the role of parents and the prevalence of childhood obesity. This study applied quantitative approach using self-administered questionnaires involving 320 parents at Seksyen 7, Shah Alam. The findings of this study revealed that parental food selection preferences and parental self efficacy have significant influence on the prevalence of childhood obesity (p<0.05, β =0. 128; p<0.05, β = 0.126). Further, subjective norms of parents have found not significantly influence towards the prevalence of childhood obesity. The findings of this study found that childhood obesity crisis starts with parents. Therefore, the parents have not played an effective role within the context of providing effective strategies for healthy eating, physical activity and dietary patterns of their children. Hence, the contribution of this study is aimed to help the parents play their role effectively to prevent childhood obesity and to provide healthy eating strategies about making healthy dietary intake.